Physical Activity and Exercise Patterns After Spontaneous Coronary Artery Dissection: Insights From a Large Multinational Registry - Chacin-Suarez, Audry S.; Bonikowske, Amanda R.; Medina-Inojosa, Jose R.; Gulati, Rajiv; Best, Patricia J.; Hayes, Sharonne N.; Tweet, Marysia S. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To assessed physical activity (PA) and exercise patterns among participants in a large multinational spontaneous coronary artery dissection (SCAD) registry. Patients and Methods: Participants with SCAD enrolled from March, 2011 to November, 2019 completed surveys including details regarding PA and exercise habits prior to SCAD, and PA counselling received from their provider after SCAD. Demographics and clinical characteristics were collected by electronic record review. Exercise prescribed to patients after SCAD was categorized according to exercise components: type, intensity, frequency, time/session, and extreme environmental conditions. Results: We included 950 participants; Mean±age was 46.8±9.5 years old at time of first SCAD; most (96.3%) were women and (77.0%) attended ≥1 cardiac rehabilitation session. Hyperlipidemia (34.3%), hypertension (32.8%), and elevated body weight (overweight=27.0%; obesity=20.0%) were the most common comorbidities. Prior to SCAD, 48.5% performed aerobic exercise ≥3 times/week and only 32.0% performed strength-building exercise regularly. PA counselling details after SCAD in 299/950 participants showed that most (93.3%) patients received some form of counselling including: exercise prescription (EXP), nonspecific recommendations, and discouraged from any exercise. Limits regarding exercise type and intensity were the most common advice among participants who received EXP. Conclusion: Insights from our study suggest that only 40% of patients were achieving current exercise recommendations for adults prior to SCAD [lower (53%) than adult U.S population; CDC, 2018] and 70% have ≥1 cardiovascular risk factors. We suggest guiding patients based on individual assessment, taking into consideration baseline PA habits, treatment, and risk factors. SCAD-tailored PA guidelines are needed for optimal EXP without compromising patient safety